Investigating the role of calcium/calmodulin-dependent protein kinases in Stagonospora nodorum - Solomon, P.; Rybak, K.; Trengove, R.; Oliver, Richard (BLACKWELL PUBLISHING, 2006)
Three genes encoding different Ca2+/calmodulin-dependent protein kinases have been characterized in the wheat phytopathogenic fungus Stagonospora nodorum. The kinases were identified from the S. nodorum genome sequence on the basis of sequence homology to known Ca2+/calmodulin-dependent protein kinases. Expression analysis determined that each of the kinases was expressed during growth in vitro and also during infection. The onset of sporulation triggered increased transcript levels of each of the kinases, particularly CpkA where an 11-fold increase in expression was observed during sporulation in planta. The role of the kinases was further determined via a reverse genetics approach. The disruption of CpkA affected vegetative growth in vitro and also sporulation. The cpkA strains produced 20-fold less spores on complex media and were unable to sporulate on defined minimal media. Infection assays showed that CpkA was not required for lesion development but was essential for sporulation at the completion of the infection cycle. Microscopic analysis revealed that the disruption of CpkA resulted in Stagonospora nodorum being unable to differentiate the mycelial knot into immature pycnidia during sporulation. A metabolite analysis of infected leaves during sporulation excluded the possible involvement of mannitol, a compound previously shown to be involved in the sporulation of Stagonospora nodorum. The disruption of CpkB did not effect growth in vitro or pathogenicity. Stagonospora nodorum strains lacking CpkC appeared unaffected during growth in planta but showed delayed lesion development and sporulation during infection.